Distinct colonization waves underlie the diversification of the freshwater sculpin (Cottus gobio) in the Central European Alpine region. (5th July 2018) - Lucek, Kay; Keller, Irene; Nolte, Arne W.; Seehausen, Ole
Abstract: Ecological speciation and adaptive radiation are key processes shaping northern temperate freshwater fish diversity. Both often involve parapatric differentiation between stream and lake populations and less often, sympatric intralacustrine diversification into habitat‐ and resource‐associated ecotypes. However, few taxa have been studied, calling for studies of others to investigate the generality of these processes. Here, we test for diversification within catchments in freshwater sculpins in a network of peri‐Alpine lakes and streams. Using 8047 and 13 182 restriction site‐associated (RADseq) SNPs, respectively, we identify three deeply divergent phylogeographic lineages associated with different major European drainages. Within the Aare catchment, we observe populations from geographically distant lakes to be genetically more similar to each other than to populations from nearby streams. This pattern is consistent with two distinct colonization waves, rather than by parapatric ecological speciation after a single colonization wave. We further find two distinct depth distribution modes in three lakes of the Aare catchment, one in very shallow and one in very deep water, and significant genomewide differentiation between these in one lake. Sculpins in the Aare catchment appear to represent an early‐stage adaptive radiation involving the evolution of a lacustrine lineage distinct from parapatric stream sculpins and the repeated onset of depth‐related intralacustrine differentiation.